Information studies and science in Vytautas Didysis university - Kaminskas, ytautas (Information & Media, 1994)
General information studies in the University consists of two levels: informatics for the beginners and computers application. Students can freely choose between them. The article describes the special education in informatics. The main subjects of these studies are shortly described.
Keywords: -